Transformasi Digital Koperasi Dan UMKM Di Kota Tanjungpinang: Model Kepemimpinan Teknologi Dalam Mendorong Inklusi Ekonomi Berbasis Kepulauan - neng suryanti nengsih; Zamzami Karim; Edward Mandala; Sri Ambar Rinah (STISIPOL Raja Haji, 2026)
Digital transformation is a crucial urgency for the sustainability of Cooperatives and Micro, Small, and Medium Enterprises (MSMEs), particularly in addressing geographical challenges in archipelagic regions like Tanjungpinang City. However, the absence of adaptive and contextual technological leadership models to drive digital transformation of cooperatives and MSMEs in island regions with limited digital infrastructure has the potential to widen economic and digital inclusion gaps. This study aims to formulate a technological leadership model that can accelerate digital adoption and drive economic equality across urban and coastal villages (kelurahan) in Tanjungpinang. The research employs a qualitative approach with a literature review method, synthesizing various secondary sources including national and international journals, government reports, and academic publications from the last decade. Data analysis was conducted descriptively through grouping, comparison, and synthesis of previous findings to identify challenges and strategic opportunities. The results suggest that effective digital transformation in Tanjungpinang requires